Career Choice to Become a Tax Consultant: Moderating Gender, Social Values and Personality - Sri Lestari Yuli Prastyatini; Putri Nolla Arthamevia (Proceeding International Conference on Accounting and Finance, 2025)
Interest in choosing a career as a tax consultant is still very low in Indonesia compared to the increasing number of taxpayers. This phenomenon is one of the reasons for conducting this research. This quantitative research aims to determine the influence of social values ​​and personality on choosing a career as a tax consultant with gender as a moderating variable. The research involved 75 accounting study program students throughout Yogyakarta who had participated in tax volunteering. Research data was collected by distributing questionnaires to respondents and analyzed using descriptive statistics with the help of IBM SPSS version 25. The findings of this research are that social values ​​and personality have a significant positive influence on choosing a career as a tax consultant. Apart from that, gender is able to strengthen the influence of the relationship between social values ​​and personality on choosing a career as a tax consultant. Adding gender as a moderating variable makes accounting study program students in Yogyakarta who have participated in tax volunteering as a different population from previous research.